2006
DOI: 10.1152/ajpheart.00951.2005
|View full text |Cite
|
Sign up to set email alerts
|

β1-Adrenoceptor blockade mitigates excessive norepinephrine release into cardiac interstitium in mitral regurgitation in dog

Abstract: Mitral regurgitation (MR) is associated with increased neuronal release of norepinephrine (NE) and epinephrine (EP) into myocardial interstitial fluid (ISF) that may be necessary in sustaining left ventricular (LV) function via activation of cardiomyocyte beta-adrenergic receptors (ARs). However, activation of neuronal beta-ARs on cardiac neurons may lead to further catecholamine release, with an attendant risk of functional deterioration. We hypothesize that a beneficial effect of beta-AR blockade may therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…1,2 In addition to these structural changes, there is development of cardiac hypertrophy and subsequent LV dysfunction in MR that are improved by ␤-adrenergic receptor blockade (␤-RB) 3 but not by angiotensin-converting enzyme inhibition or angiotensin type 1 receptor blockade, 4,5 suggesting that the adrenergic system is more central to the pathophysiology of VO of isolated MR. Moreover, studies in humans and dogs have demonstrated an increase in adrenergic drive even in a mild compensated state of isolated MR, 6,7 most likely attributable to the early achievement of preload reserve.…”
mentioning
confidence: 99%
“…1,2 In addition to these structural changes, there is development of cardiac hypertrophy and subsequent LV dysfunction in MR that are improved by ␤-adrenergic receptor blockade (␤-RB) 3 but not by angiotensin-converting enzyme inhibition or angiotensin type 1 receptor blockade, 4,5 suggesting that the adrenergic system is more central to the pathophysiology of VO of isolated MR. Moreover, studies in humans and dogs have demonstrated an increase in adrenergic drive even in a mild compensated state of isolated MR, 6,7 most likely attributable to the early achievement of preload reserve.…”
mentioning
confidence: 99%
“…There is a strong impetus for the use of ␤-receptor blockers in the treatment of MR (15) given that there is increased sympathetic drive in both the human (8) and dog (4,9,17). Although initial sympathetic drive is a necessary compensatory mechanism in MR, long-term activation may have a cytotoxic effect on cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sympathetic drive follows the initial recruitment of preload reserve in the early phase of MR in the human (8) and dog (4,9,17). Using the microdialysis technique in healthy open-chest canines, we have shown that there is compartmentalized norepinephrine and epinephrine release into the LV interstitial fluid space during electrical stimulation of the stellate ganglion (4,17).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The sympathetic nervous system is activated in severe mitral regurgitation, 24 and in a dog model of mitral regurgitation, ␤ 1 -receptor blockade decreases the adverse effects of excess norepinephrine release on myocardial function. 25 In large clinical trials, ␤-blockers decreased the risk of sudden death, 4,5 an occasional catastrophic event that is known to occur in asymptomatic patients with mitral regurgitation. 26 …”
Section: Discussionmentioning
confidence: 99%